TRAINING AND ASSISTANCE IN THE DEVELOPMENT OF LEARNING OUTCOME ASSESSMENT MATERIALS HIGH-ORDER THINKING SKILLS FOR HIGH SCHOOL MATHEMATICS TEACHERS IN SOUTH TANGERANG - Elin Herlinawati; Selly Anastassia Amellia Kharis; Darsih Idayani; Hasoloan Siregar; Siti Umamah Naili Muna (LP2M Universitas Ibrahimy, 2023)
High Order Thinking Skill (HOTS) is students' ability to process knowledge and ideas in a certain way to give them new knowledge and implications. The general perception regarding HOTS questions is that they are high-level questions. Most teachers adopt olympic questions as HOTS questions due to a misperception that HOTS questions are difficult, even though HOTS questions can be made in various difficulty levels: low, medium, and high. In addition, the substantive aspect of Mathematics, especially the application of Mathematics in life, is also one of the problems in developing HOTS questions. The method of implementing community service (PkM) is by training and assisting in preparing SMA-level Mathematics HOTS questions. The results of this PkM activity are: (1) Increased knowledge and understanding of teachers in the technique of developing HOTS questions which can be seen in an increase in the average pre-test and post-test results by 9%, (2) Improved mathematical skills in the use of concepts and applied Mathematics on HOTS questions. This can be seen from the questions made by the teachers in this PkM activity, and (3) the participants' satisfaction with this PkM activity is shown by the questionnaire results with a satisfaction range of 85.71% - 96.43%.